Perinatal dysfunction of innate immunity in cystic fibrosis: cystic fibrosis - Jaudas, Florian; Bartenschlager, Florian; Shashikadze, Bachuki; Santamaria, Gianluca; Reichart, Daniel; Schnell, Alexander; Stöckl, Jan Bernd; Degroote, Roxane L.; Cambra, Josep M.; Graeber, Simon Y.; Bähr, Andrea; Kartmann, Heike; et al. (Science translational medicine, 2025)
In patients with cystic fibrosis (CF), repeated cycles of infection and inflammation eventually lead to fatal lung damage. Although diminished mucus clearance can be restored by highly effective CFTR modulator therapy, inflammation and infection often persist. To elucidate the role of the innate immune system in CF etiology, we investigated a CF pig model and compared these results with those for preschool children with CF. In newborn CF pigs, we observed changes in lung immune cell composition before the onset of infection that were dominated by increased monocyte infiltration, whereas neutrophil numbers remained constant. Flow cytometric and transcriptomic profiling revealed that the infiltrating myeloid cells displayed a more immature status. Cells with comparably immature transcriptomic profiles were enriched in the blood of CF pigs at birth as well as in preschool children with CF. This pattern coincided with decreased CD16 expression in the myeloid cells of both pigs and humans, which translated into lower phagocytic activity and reduced production of reactive oxygen species in both species. These results were indicative of a congenital, translationally conserved, and functionally relevant aberration of the immune system in CF. In newborn wild-type pigs, CFTR transcription in immune cells, including lung-derived and circulating monocytes, isolated from the bone marrow, thymus, spleen, and blood was below the detection limits of highly sensitive assays, suggesting an indirect etiology of the observed effects. Our findings highlight the need for additional immunological treatments to target innate immune deficits in patients with CF.
Gesehen am 31.07.2025